Burr Reduction of Micro-milled Microfluidic Channels Mould Using a Tapered Tool - Saptaji, Kushendarsyah; Subbiah, Sathyan (Elsevier Ltd, 2017)
Moulds with micro-sizes features needed for many applications, such as for hot embossing, can be manufactured using micro-milling process. However, the burrs formed in the micro-milling process are a challenge that needs to be addressed. The burr sizes are comparable to the micro-milled feature sizes and the common types of burr seen being the top/side and exit burrs. The use of a tapered geometry micro-milling tool is investigated in this paper that enables reduction in both the top and exit burrs. The straight and tapered micro-milling tools of various angles are used and the burrs formed are observed. Micro-milling experiments are conducted on an aluminium alloy by producing common positive features seen in the mould for the production of polymer microfluidic devices. The results show that the burr reduction can be attributed due to the increase of the taper angle. It is seen that the tapered tool not only substantially reduces the top burrs, but also leaves behind inclined walls which further help in reducing exit burrs formed during the subsequent finish face milling. Furthermore, embossing trials performed with the micro-milled tapered geometry moulds show improved performance not only because burrs are reduced and also because the taper eases mould release.